2020
DOI: 10.3390/rs12020236
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Winter Wheat Yield Based on Multi-Source Data and Machine Learning in China

Abstract: Wheat is one of the main crops in China, and crop yield prediction is important for regional trade and national food security. There are increasing concerns with respect to how to integrate multi-source data and employ machine learning techniques to establish a simple, timely, and accurate crop yield prediction model at an administrative unit. Many previous studies were mainly focused on the whole crop growth period through expensive manual surveys, remote sensing, or climate data. However, the effect of selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
113
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(115 citation statements)
references
References 114 publications
2
113
0
Order By: Relevance
“…The correlation between SPOT images and SPAD readings was similar to results between aerial images and SPAD readings, indicating that SPOT images may have potential abilities for detecting the chlorophyll levels and nitrogen stress of maize. Meanwhile, it is really a challenge to predict the crop yields in developing countries like China, as the varieties and management practice of crops vary greatly [ 23 , 24 ]. Thus, accurately acquiring the leaf chlorophyll contents and predicting the yields are crucial for agricultural practices, which is of vital importance for stable growth and development of the economy and society.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between SPOT images and SPAD readings was similar to results between aerial images and SPAD readings, indicating that SPOT images may have potential abilities for detecting the chlorophyll levels and nitrogen stress of maize. Meanwhile, it is really a challenge to predict the crop yields in developing countries like China, as the varieties and management practice of crops vary greatly [ 23 , 24 ]. Thus, accurately acquiring the leaf chlorophyll contents and predicting the yields are crucial for agricultural practices, which is of vital importance for stable growth and development of the economy and society.…”
Section: Introductionmentioning
confidence: 99%
“…They achieved higher accuracy and concluded that it would be easier to generate an annual mapping of wheat for using the satellite data as it contributes to the reduction of errors. Han et al [52] investigated a modelling approach for predicting winter wheat yield by integrating soil data, climate data and vegetation index data. The authors employed eight typical machine learning models, and the results showed that SVM, GPR and RF were the top three best techniques to predict yields.…”
Section: Wheat Yield Predictionmentioning
confidence: 99%
“…Several technologies and related tools were discovered in solving coffee operations and production problems. Han et al [41] applied SVM to increase production crop through yield prediction (90%). Pinto et al [19] used the image processing technique for sorting defective coffee beans with higher efficiency of 72.4-98.7%.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment approach implemented in this work has been inspired by Kamilaris et al [41]. The application of big data in agriculture has recently been gaining attention, which is evidently realized from Table 1.…”
mentioning
confidence: 99%